Robert De Beaugrande’s textual standards and its impact on understanding the Hadith of Prophetic Medicine of Talbīna - Abd Gani, Muhammad Izuan; Ali, Asem Shehadeh Saleh (Anka Publishers, 2022)
This study analyzed the text structure from the perspective of modern linguistics by applying Robert de Beaugrand's textual standards to the hadith of prophetic medicine on the therapeutic quality of a type of food known as Talbīna. The textual standards proposed by De Beaugrand are among the essential linguistic tools that are significant in dissecting the construction of a text, achieving its textual coherence, conceptual interdependence, and communicativeness. The study aims to uncover the textual elements: cohesion, coherence, intentionality, acceptability, situationally, informativity, and intertextuality, besides their impact on the understanding of Prophetic discourse. The approach of this study is qualitative and based on textual analysis. This approach addresses the description, analysis, and explanation of the hadith in the light of text linguistics, highlighting the elements of the textual standards and identifying their importance for ensuring the coherence and interdependence of the hadith and their impact on its understanding. The results indicate that this hadith has those seven elements of the textual standards, starting with the cohesion, which consists of the aspects of availability; reference, ellipsis, and conjunction, and the criterion of coherence and its elements such as situation, context, metaphor and correlation, and the manifestations of intentionality and acceptability in the hadith are revealed, as well as the criteria of situationality, informativity, and intertextuality. All these elements help maintain the coherence, conceptual interdependence, and communicativeness of the hadith and their impact on its interpretation and understanding by the receptors. Keywords: text linguistics, textual standards, textual measures, Robert De Beaugrande, prophetic medicine, hadith of Talbīna.